Inflation dynamics in South Africa - Leshoro, Temitope Lydia (My University, 2016)
The design and implementation of the monetary policy in South Africa has been based on the idea of a trade-off between inflation and output growth. However, there is no consensus among empirical investigations on the existence of Phillips curve in the present times. While the South African Reserve Bank (SARB) has instrument independence, it does not have goal independence, which implies that there is coordination between the monetary policy and other macroeconomic policies. Thus, if the SARB objectives are in line with the other policy objectives, there should be a relationship between monetary variables and real variables. This therefore shows that in the long-run, monetary policy cannot single-handedly bring about both sustained economic growth and employment creation (SARB, 2014). Thus this study explored inflation dynamics in South Africa by using the Hybrid new Keynesian Phillips curve (HNKPC) and the augmented Gordon’s models. The study firstly estimated the Hybrid new Keynesian Phillips curve model with a view to determine whether Phillips curve exists and ascertain whether the backward-looking or forward-looking components drive inflation dynamics in South Africa using OLS and GMM estimation techniques. The results show that the Phillips curve does not exist in South Africa using various measures of demand-side variable. These findings are robust across estimation methodologies as well as different measurements of inflation expectations and data frequency. While the findings indicated that economic agents in South Africa are both rational and adaptive in predicting inflation, the results clearly showed the dominance of forward looking component over the backward looking element in driving inflation. Secondly, given the focus of the South African monetary authority in maintaining stable inflation rates and the fact that monetary policy need to go hand-in-hand with other policies in order to ensure stable inflation and economic growth (Gruen, Pagan and Thompson, 1999), this study considered the expanded Gordon’s model with a particular focus on how fiscal policy determines the inflation process in South Africa. The purpose of the Gordon’s chapter is to verify the existence or non-existence of Phillips curve in an expanded model, within the context of an augmented “triangle” model while including the monetarist and fiscal side variables, thereby checking whether the PC relationship of recent studies is robust to model specification. Thus, the augmented Gordon’s model was estimated using a holistic approach of including the fiscalist, monetarist and the structuralist schools of thought, using the Vector autoregressive (VAR), vector error correction model (VECM) and innovation accounting techniques. The results confirm the non-existence of PC whereby output growth maintained a negative relationship with inflation rate, signifying no trade-off despite the expanded specification, while the results from output-gap model are inconclusive. Further results showed that the demand-side, fiscal factors and some of the structural variables contribute more to the inflation dynamics in South Africa. Thus the changes in inflation rate are as a result of changes in output growth, government deficit, electricity price and exchange rate. The results confirmed that the Fiscal Theory of the Price Level (FTPL) applies to the South African economy, whereby not only monetary policies should be considered in controlling inflation, but also fiscal policies. On the other hand, the importance of the determinants of inflation rate is not sufficient in observing the inflation dynamics in South Africa; therefore, this study concluded by investigating the level at which inflation becomes detrimental to output growth. In the context of the low levels of economic growth and high levels of unemployment in South Africa, the study analysed the output growth implications of the inflation targeting monetary policy of the South African Reserve Bank that targets an inflation band between three and six percent. Using the Threshold Autoregressive (TAR) and the Sample Splitting Threshold Regression (SSTR) techniques, this study investigated the nonlinear inflation-growth nexus in South Africa with the purpose of identifying the inflation rate band that optimize output growth. The results showed that South Africa is able to accommodate a higher level of inflation beyond the current inflation target band by increasing the band to between seven and nine percent in order to enhance output growth. Our findings support the argument of studies that indicate that moderately higher inflation rate will not be harmful to the economy.
Thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in the FACULTY OF COMMERCE LAW AND MANAGEMENT SCHOOL OF ECONOMICS AND BUSINESS SCIENCES at the UNIVERSITY OF THE WITWATERSRAND
Keywords: Inflation (Finance)--South Africa; Keynesian economics; Monetary policy--South Africa; Phillips curve